Analysis of brain activation and effective connectivity during self-paced unilateral and bilateral finger tapping using functional magnetic resonance imaging in patients with temporal lobe epilepsy - Yusoff, Bazli Md (2021)
Background: Temporal lobe is the most frequent site of origin of partial seizures. Patients with Temporal Lobe Epilepsy (TLE) represent approximately two thirds of the intractable seizure population. Objectives: This study aims to compare the area of activation in between healthy subjects and TLE patients as a result of increase in blood oxygen level in different parts of the brain during self-paced unilateral and bilateral finger tapping. In addition, this study also aims to compare the effective connectivity in between region of interest in Healthy subjects and TLE patients during self-paced unilateral and bilateral finger tapping. Methodology: This study involves 12 healthy subjects and 12 TLE patients. All of them undergone functional magnetic resonance imaging (fMRI) where they performed self-paced unilateral and bilateral finger tapping. The images were then pre-processed and underwent first level analysis using Statistical Parametric Mapping (SPM). Second level analysis were then performed to compare the area of activation in healthy subjects and TLE patients. For effective connectivity, two regions of interest were chosen which represent visual and motor regions. Three models tested in between each region of interest which were bidirectional, visual to motor and motor to visual. These tests were conducted in each brain hemispheres of both healthy subjects and TLE patients. Results: In both healthy subjects and TLE patients, first level analysis showed intense activation at the visual area. Second level analysis was performed comparing the two group of samples, using two samples t-test, familywise error rate (FWE) p < 0.05, healthy subjects showed more areas of significant activation. For effective connectivity, in healthy subjects, visual to motor was the dominant model with average value of 0.03Hz bilaterally. In TLE subjects, on the right hemisphere, a contrary result was observed whereby motor to visual area was the dominant model. On the left hemisphere, the same model as healthy subjects was the dominant model, visual to motor, but with higher average value of 0.1Hz. Conclusion: This study found that there were less area of brain that has significant activation in TLE patients during motor activity. TLE brains also exhibit different effective connectivity whereby in the right hemisphere, motor area exerts more influence on the visual area and in the left hemisphere, visual area exerts significantly more influence on the motor area. These findings suggest that there is alteration of the motor networks in TLE patients.